Enhancing Breastfeeding Mothers’ Science Literacy in Choosing Safe Hormonal Contraceptives for Breast Milk Production: A Contextual Educational Study - Olivia Nency; Ifqiyatus Sholehah; Jean August Amanda; Effen Effen; Siti Nurasia; Pearl Jannah; Ricky Andila Safitri; Windy Nurfauziah (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to compare the effects of different progestin-only hormonal contraceptives (injection, pills, and implants) on the duration of breastfeeding among hormonal birth control users. A total of 210 breastfeeding mothers using progestin-only contraceptives were included in this study. The participants were divided into three groups: 70 mothers using contraceptive pills, 70 using contraceptive injections, and 70 using contraceptive implants. The duration of breastfeeding was recorded as the dependent variable. The data were analyzed using one-way Analysis of Variance (ANOVA) to compare the average breastfeeding duration between the three groups. The results showed no significant difference in the duration of breastfeeding among the three groups. The Tukey HSD test indicated a p-value of 0.195, which is greater than 0.05, suggesting that the use of progestin contraceptive injections, pills, or implants did not significantly affect the duration of breastfeeding. This study concludes that there is no significant difference in breastfeeding duration between mothers using different types of progestin-only hormonal contraceptives. Health workers should provide clear information to mothers about the safety and potential effects of different contraceptive methods on breastfeeding, enabling them to make informed choices